Third dimension a comparative history of mountains in the modern era. - Mathieu, Jon (White Horse Press, 2013)
A pioneering examination of the three-dimensionality of the Earth from the perspective of history and the humanities, this book considers the variegated world of mountains and their development during the last 500 years. At the book's heart stands the question of whether and in what way the 'three-dimensional history' of mountain people may reveal distinctive forms of development.